The Reaction Kinetics of 3-Hydroxybenzoate 6-Hydroxylase from Rhodococcus jostii RHA1 Provide an Understanding of the para-Hydroxylation Enzyme Catalytic Cycle - Sucharitakul, Jeerus (American Society for Biochemistry and Molecular Biology, 2013)
3-Hydroxybenzoate 6-hydroxylase (3HB6H) from Rhodococcus jostii RHA1 is an NADH-specific flavoprotein monooxygenase that catalyzes the para-hydroxylation of 3-hydroxybenzoate (3HB) to form 2,5-dihydroxybenzoate (2,5-DHB). Based on results from stopped-flow spectrophotometry, the reduced enzyme-3HB complex reacts with oxygen to form a C4a-peroxy flavin with a rate constant of 1.13 ± 0.01 × 10(6) m(−1) s(−1) (pH 8.0, 4 °C). This intermediate is subsequently protonated to form a C4a-hydroperoxyflavin with a rate constant of 96 ± 3 s(−1). This step shows a solvent kinetic isotope effect of 1.7. Based on rapid-quench measurements, the hydroxylation occurs with a rate constant of 36 ± 2 s(−1). 3HB6H does not exhibit substrate inhibition on the flavin oxidation step, a common characteristic found in most ortho-hydroxylation enzymes. The apparent k(cat) at saturating concentrations of 3HB, NADH, and oxygen is 6.49 ± 0.02 s(−1). Pre-steady state and steady-state kinetic data were used to construct the catalytic cycle of the reaction. The data indicate that the steps of product release (11.7 s(−1)) and hydroxylation (36 ± 2 s(−1)) partially control the overall turnover.